MENCARI JATI DIRI? (Relasi antara Nasionalisme dengan Pendidikan) - Husain Haikal (Khazanah Pendidikan, 2008)
This paper tries to give a closer look at the relationship between nationalism and education during the Dutch colonization which had born the national leaders. They were leaders who had found their true identity as leaders. They are our founding fathers who never thought of anything other than the national interest. Among them are: HOS Tjokroaminoto, dr. Soetomo, Ki Hajar Dewantara, and Soekarno (the Indonesian Proclamator) Key words: self identity, the founding fathers